The Application of Equivalent Age Concept to Sand Concrete Compared to Ordinary Concrete - Nabil Bella; Ilham Aguida Bella; Aissa Asroun (Advances in Civil Engineering)
In this research the equivalent age concept was used, in order to simulate strength development of heat treated sand concrete compared with ordinary concrete at different temperature, 35, 55, and 70°C, and validate the simulation results with our experimental results. Sand concrete is a concrete with a lower or without coarse aggregate dosage; it is used to realize thin element as small precast prestressed beams, in injected concrete or in regions where sand is in extra quantity and the coarse aggregate in penury. This concrete is composed by principally sand, filler, superplasticizer, water, and cement. The results show that the simulation of ordinary concrete was acceptable with an error lower than 20%. But the error was considerable for the sand concrete. The error was due to large superplasticizer dosage, which modified the hardening of sand concrete; the most influent parameter in Arrhenius law is apparent energy activation, to search for the value of the activation energy which gives the best simulation; a superposition is used of two curves of different temperature and with superplasticizer dosage 4% and several values of activation energy, 15, 20, 25, and 30 × 10 kcal. The simulation becomes ameliorated with the adequate value of activation energy.